Futurs enseignants en stage au pays des Massaïs : from Me to We ? - Eva Lemaire (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article is based on the international training practicum program experienced by 14 Canadian students specializing in Education, as they taught in a Maasai school, in partnership with two NGOs, namely Free the Children and Me to We. In terms of methodology, this research is grounded in data derived from (1) semi-directed interviews with the students before departure, during the practicum, and back home in Canada, and (2) data derived from field notes and class observation in Kenya. The study explores how this experience abroad enhances students’ engagement in terms of intercultural and global citizenship education. To what extent does encountering local students, teachers and the community at large foster a more complex understanding of the concept of “culture” ? How does cross-cultural teaching challenge students’ perceptions of educational culture ? The article emphasizes the challenges students face as they try to implement a cross-cultural learning space. It highlights the difficulty in balancing respect for their Kenyan counterparts’ culture, a desire to implement change by presenting new teaching methods and a willingness to minimize cultural variance. This article also questions the risk of misinterpretation when students face struggles with their teaching, putting the onus of this struggle on cultural issues when their lack of experience in teaching might be involved, as this practicum is often their first teaching experience. Finally, this study indicates how this program has had a different impact on the students involved in terms of intercultural and global citizenship education, stressing the importance of formal knowledge teaching beyond the experiential aspects of this program.